2016
DOI: 10.1159/000447963
|View full text |Cite
|
Sign up to set email alerts
|

Modifiable Factors Associated with Cognitive Impairment in 1,143 Japanese Outpatients: The Project in Sado for Total Health (PROST)

Abstract: Background/Aims: Evidence on modifiable factors associated with cognitive impairment in Japanese patients is scarce. This study aimed to determine modifiable factors for cognitive impairment in a Japanese hospital-based population. Methods: Subjects of this cross-sectional study were 1,143 patients of Sado General Hospital (Niigata, Japan) registered in the Project in Sado for Total Health (PROST) between June 2008 and September 2014. We assessed disease history, body mass index (BMI), leisure time physical ac… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
28
0

Year Published

2017
2017
2024
2024

Publication Types

Select...
8

Relationship

2
6

Authors

Journals

citations
Cited by 31 publications
(28 citation statements)
references
References 28 publications
0
28
0
Order By: Relevance
“…Consecutive low concentrations of EGCG in the brain are thought to be important for brain plasticity. Epidemiological data shows that drinking green tea daily reduces the risk of cognitive decline is accumulating [35] , [36] , [37] . Our data suggests a reason for the daily ingestion of green tea namely to prevent age-related cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Consecutive low concentrations of EGCG in the brain are thought to be important for brain plasticity. Epidemiological data shows that drinking green tea daily reduces the risk of cognitive decline is accumulating [35] , [36] , [37] . Our data suggests a reason for the daily ingestion of green tea namely to prevent age-related cognitive dysfunction.…”
Section: Discussionmentioning
confidence: 99%
“…Some studies have shown that low BMI is a risk factor for dementia or cognitive impairment [ 2 , 11 , 21 23 ]. Recently, a large cohort study showed that underweight individuals (BMI <20 kg/m 2 ) are at an increased risk of dementia in all age groups ≥40 years [ 22 ].…”
Section: Discussionmentioning
confidence: 99%
“…In European and North American countries, a large body of evidence suggests that being overweight or obese can increase one’s risk toward developing dementia [ 8 10 ]. In contrast, some studies reported being underweight as a risk factor [ 8 ]; a hospital-based epidemiologic study conducted in Japan found that being underweight may be a risk factor for cognitive impairment [ 11 ]. The association between body mass and dementia or cognitive impairment remains unclear, however, and further elucidation in population-based studies is warranted.…”
Section: Introductionmentioning
confidence: 99%
“…Age, sex, hsCRP level, body mass index (BMI), history of stroke, ischemic heart disease, hypertension, diabetes, oral health‐related variables (tooth brushing, history of gum swelling, and professional tooth cleaning), smoking and alcohol consumption, and dietary characteristics (intake of vegetables, fruit, and green tea) were considered as covariates in view of previous reports on risk factors for cognitive impairment (Bleckwenn et al, ; Cukierman, Gerstein, & Williamson, ; Elias, Elias, Sullivan, Wolf, & D'Agostino, ; Kitamura et al, ; Paganini‐Hill, White, & Atchison, ; Panza et al, ; Park, Park, Jun, Choi, & Suh, ; Patel, Coshall, Rudd, & Wolfe, ; Swan & Lessov‐Schlaggar, ; Watanabe et al, ). Age, sex, BMI, and blood pressure (BP) were recorded as part of the PROST registration procedure.…”
Section: Methodsmentioning
confidence: 99%